Síntese de heterocíclicos fotoluminescentes e-lapachonas arilamino substituídas : aplicações em biologia celular e na terapêutica do câncer - Eduardo Henrique Guimarães da Cruz (2013)
Two new lapachol derivatives, a nor--lapachone and its respective phenazine, benzothiadiazole-triazole-linked have been synthesized and characterized by 1D and 2D NMR spectroscopy. Their photophysical properties were investigated. This work also describes the molecular architecture based on two substitutions on the important 2,1,3-benzothiadiazole (BTD) core at positions 4- and7-. One side is substituted with a group capable of performing an ESIPT (excited-state intramolecular proton transfer), a stabilizing process, and the other side is substituted with a triazole-containing group. This triazole ringacts as a linker between the BTD core and a group of known antitumoral activity, a quinoidal derivative of nor--lapachone. This novel compound had its antitumoral activity evaluated against twenty cancer cell lines and against normal cells, V79, L-929 and PBMC. The quinone was very active against all cancer cell lines and it was more active than doxorubicin (positive control) against six cell lines. The quinone also shows lowercitotoxity to normal cell lines, when compared to the positive control. Due to their interesting photophysical properties and good fluorescence, bioimaging experiments were conducted with the phenazine derivative and this dye was tested as a fluorescent cellimagingprobe, thus showing its preferable cellular location in the perinuclear region of MDA-MB-231 cancer cells (a breast invasive cancer cell lineage). Aiming at obtaining of new compounds with antitumor activity the synthese of -lapachone derivatives with some different arylamino substituents in ring C were performed. These compounds weresubmitted to biological studies.